Volume 7: Turbomachinery, Parts a and B 2009
DOI: 10.1115/gt2009-60285
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Unsteady Flow in an Aspirated Counter-Rotating Compressor Using the Nonlinear Harmonic Method

Abstract: A multistage frequency domain (Nonlinear Harmonic) Navier-Stokes unsteady flow solver has been used to analyze the flow field in the MIT (rotor/rotor) aspirated counter-rotating compressor. The numerical accuracy and computational efficiency of the Nonlinear Harmonic method implemented in Numeca’s Fine/Turbo CFD code has been demonstrated by comparing predictions with experimental data and nonlinear time-accurate solutions for the test case. The comparison is good, especially considering the big savings in tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Figure 2 depicts the meridional view of the computational domain. Previous experience with simulating the CRAC geometry by Knapke et al [25] and grid dependency studies by Guidotti and Turner [26,27] and Knapke [28] have shown that the results are sensitive to the spanwise grid resolution. For this reason, a spanwise cell count of 172 was chosen.…”
Section: Numerical Approachmentioning
confidence: 99%
“…Figure 2 depicts the meridional view of the computational domain. Previous experience with simulating the CRAC geometry by Knapke et al [25] and grid dependency studies by Guidotti and Turner [26,27] and Knapke [28] have shown that the results are sensitive to the spanwise grid resolution. For this reason, a spanwise cell count of 172 was chosen.…”
Section: Numerical Approachmentioning
confidence: 99%
“…The nonlinear harmonic (NLH) method has been tested and validated against several turbomachinery cases, with the result that the time savings seemed to be significant over the time-domain unsteady method. 7,8 The first priority of this study is directed toward demonstrating those claims in a counterrotating research compressor (CRRC), as the NLH method is relatively new with limited validation. Apart from this, there are several issues of interest.…”
Section: Focus Of Research Effortmentioning
confidence: 99%
“…At present, however, there are few studies on unsteady flow mechanism of counter-rotating compressor. The Turner research group of University of Cincinnati 29,30 has conducted the numerical simulations of MIT counter-rotating compressor, but mainly shed light on analyzing the compressor performance. Besides, Limin et al 31 and Mao and Liu 32 of Northwestern Polytechnical University have performed unsteady numerical simulations in the subsonic counter-rotating compressor under NS conditions, respectively.…”
Section: Introductionmentioning
confidence: 99%